Nasal irrigation with various solutions for adults with allergic rhinitis: A protocol for systematic review and meta-analysis of randomized controlled trials - Widuri, Asti; Rianto, Bambang Udji Djoko; Indrawati, Luh Putu Lusy; Nugraha, Ranggaputra; Wahab, Abdul (Lippincott Williams and Wilkins, 2022)
Background: Nasal douching or irrigation has been recommended for adjunctive therapy of sinonasal diseases including allergic rhinitis (AR) for many years. Previous study reported large-volume high-pressure device as an effective standard application, but the solutions was remains controversy. This study systematically review the clinical efficacy of nasal irrigation with various solutions for adults with AR from medical literature. Methods: This research systematically asses clinical trial about nasal irrigation with various solutions for adults with AR from medical literature. The sources were PubMed, ProQuest, Scopus, Cochrane Register of Controlled Trials databases, and gray literature from google scholar and RAMA repository limited to English and Bahasa Indonesia language articles, published from January 2017 to July 2022. Only randomized controlled trials involving the human subjects studies will be included. The inclusion criteria research must be related to nasal irrigation for AR, and should be full texted available. Literature management, screening, data extraction will use Rayyan.ai tools. The quality assessment of qualified paper and risk of bias will be assessing independent conducted by 2 reviewer with risk of bias 2. We will use Review Manager (RevMan) Computer program Version 5.4. The Cochrane Collaboration, 2020 tools to produce the systematic review and meta-analysis. Results: After completion of the study process, the data analysis and review will be reported. The results will be publicized through a peer-review journal publication. Conclusion: The results of the systematic review will summarize the efficacy of various nasal irrigation for adults with AR, so it can be used as clinician recommendation. Copyright © 2022 the Author(s). Published by Wolters Kluwer Health, Inc.